A numerical investigation for heat transfer enhancement possibility for a novel perforated twisted hyperbolic turbulator (PTHT) inside a heated tube - Bing Mei; Azher M. Abed; Pinank Patel; Ankur Kulshreshta; Hamdi Ayed; Abir Mouldi; Ibrahim Mahariq (Case Studies in Thermal Engineering)
This study unveils a specialised swirl flow generator called the twisted hyperbolic turbulator for implementation in heat exchangers. The design of this geometry aims to induce bidirectional swirling flow. The water fluid flows through a heated tube at Reynolds numbers ranging from 2316 to 5096. This study examined the thermal-frictional effects of the new turbulator at various twisting angles ranging from 60 to 360°. The results indicated that as the twist angle rises, heat transfer also increases because of the fluid's intensified swirling and radial motion. Under ideal circumstances, a twist angle of 360° results in a notable increase in heat transfer by 256 % and a pressure drop by 625 %, accompanied by a TEF of 1.84. Longitudinal perforations were added to the selected turbulator at varying dimensionless distances (R = h/r) from the center, ranging from 9 to 3.6, with dimensionless hole diameters (P = h/d) ranging from 9 to 4.5. The results indicated that as the hole distance from the center of the tube increased, the TEF decreased while increasing the diameter of the perforations led to an improvement in TEF. The optimal configuration was found to be at P = 4.5, located at R = 6, resulting in a TEF of 2.02.